Efektivitas Metode Resitasi dengan Menggunakan Aplikasi Chemsketch Pada Materi Hidrokarbon Terhadap Meningkatkan Kemampuan Hasil Belajar Siswa - Riza Oktariana; Fitri Refelita (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Recitation method by using a learning medium in the form of application needed to be trained and optimized for students in the learning process; one of them is Chemsketch application. The purpose of this study was to analyze the effectiveness of the recitation method using the Chemsketch application to improve student learning outcomes on hydrocarbon material. This research was conducted in the academic year 2022/2023 at SMA Negeri 1 Hulu Kuantan with the main material being hydrocarbons. The method used in this study was quasi-experimental where the subjects in this study consisted of two classes, namely the experimental class and the control class. The instruments used in the study were pretest-posttest, interviews, and documentation to strengthen the data obtained. The results of the posttest study showed a significance value (2-tailed) of 0 <0,05, indicating that there was a significant difference between the experimental class and the control class. In addition, the average N-gain ability of experimental class students is 47,63% in the high category and 33,33% in the medium category. The results of this study are expected to help teachers improve student learning outcomes by using the Chemsketch application with recitation method.